2012
DOI: 10.1590/s1807-76922012005000005
|View full text |Cite
|
Sign up to set email alerts
|

Accrual anomaly in the Brazilian capital market

Abstract: This paper analyzes the phenomenon known as accrual anomaly in Brazil. In particular, we examine two hypotheses: (a) that the earnings expectation included in the stock price fails to reflect the difference in persistence of the earnings components (accruals and cash flows); and (b) that the construction of a hedge portfolio by taking a long (short) position in assets with low (high) accruals generates consistently abnormal returns. The data set includes nonfinancial firms listed on the BM&FBOVESPA between 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
4
1
5
Order By: Relevance
“…Contrary to the bulk of international evidence, Takamatsu and Fávero (2013) and Cupertino, Martinez, and Costa (2012) document that the market agents correctly price the accrual component of earnings and that there is no accrual anomaly in the Brazilian market. Other studies analyze the relevance of annual earnings and cash flow to market agents.…”
Section: The Relevance Of Quarterly Data Analysis and Emerging Marketmentioning
confidence: 70%
“…Contrary to the bulk of international evidence, Takamatsu and Fávero (2013) and Cupertino, Martinez, and Costa (2012) document that the market agents correctly price the accrual component of earnings and that there is no accrual anomaly in the Brazilian market. Other studies analyze the relevance of annual earnings and cash flow to market agents.…”
Section: The Relevance Of Quarterly Data Analysis and Emerging Marketmentioning
confidence: 70%
“…Empirical evidence on the accruals anomaly in the Brazilian market is still inconclusive. While some studies point to weak evidence or even no evidence at all (Cupertino et al., 2012; Silva Filho & Machado, 2013; Takamatsu & Fávero, 2013), more recent studies have presented results that suggest the existence of an accruals anomaly for firms listed on the Brazilian Stock Market (Moreira et al., 2019; Martins et al., 2019). However, considering the characteristics of an emerging economy like Brazil, we believe the evidence can become clearer by controlling for factors related to corporate governance.…”
Section: Theoretical Design and Research Hypothesismentioning
confidence: 99%
“…Cupertino et al. (2012) analyzed the existence of the accruals anomaly in Brazil and found no evidence of the occurrence of such a phenomenon. In similar studies, Takamatsu and Fávero (2013) and Silva Filho and Machado (2013) concluded that no significant abnormal returns were achieved in an accrual‐based investment strategy, indicating that investors in Brazil were able to correctly interpret and price accounting data.…”
Section: Introductionmentioning
confidence: 99%
“…La aceptación del valor razonable, por académicos y profesionales de la contabilidad, está justamente enmarcada en el paradigma de la utilidad para el decisor; elementos de los estados financieros comienzan a ser valorados a precios de mercado o actuales (Castellanos Sánchez, 2010;Da Silva Macedo, Reis Machado, Versa Machado y Cardoso Mendonça, 2013). La eficiencia de información en el mercado de capitales se torna en un factor relevante para apoyar las expectativas de los accionistas en relación con sus inversiones (Madeiros Cupertino, Affonso da Costa y Lopo Martinez, 2012;Tresman Zortea, Caio Galdi, Soares Monte-Mor y Beiruth, 2017).…”
Section: Introductionunclassified